Bank governance, regulation and risk taking - Laeven, Luc; Levine, Ross (Journal of Financial Economics, 2009)
This paper conducts the first empirical assessment of theories concerning risk taking by banks, their ownership structures, and national bank regulations. We focus on conflicts between bank managers and owners over risk, and we show that bank risk taking varies positively with the comparative power of shareholders within the corporate governance structure of each bank. Moreover, we show that the relation between bank risk and capital regulations, deposit insurance policies, and restrictions on bank activities depends critically on each bank's ownership structure, such that the actual sign of the marginal effect of regulation on risk varies with ownership concentration. These findings show that the same regulation has different effects on bank risk taking depending on the bank's corporate governance structure.